If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(8 + 5p) = p + -8 (8 * -5 + 5p * -5) = p + -8 (-40 + -25p) = p + -8 Reorder the terms: -40 + -25p = -8 + p Solving -40 + -25p = -8 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -40 + -25p + -1p = -8 + p + -1p Combine like terms: -25p + -1p = -26p -40 + -26p = -8 + p + -1p Combine like terms: p + -1p = 0 -40 + -26p = -8 + 0 -40 + -26p = -8 Add '40' to each side of the equation. -40 + 40 + -26p = -8 + 40 Combine like terms: -40 + 40 = 0 0 + -26p = -8 + 40 -26p = -8 + 40 Combine like terms: -8 + 40 = 32 -26p = 32 Divide each side by '-26'. p = -1.230769231 Simplifying p = -1.230769231
| 4x^4+8x^2+9= | | 12(5n+3)= | | 5x+81=8x | | -0.16b=3 | | 0=-4.9t^2+29.4t | | 25+-40= | | log(5x+20)=3 | | y+0.3y-2.2=-5.8(y+6.5) | | 6tx(-3)=198 | | n/5+0.6=2 | | 1(2/5)n-2n=33/20 | | 28-5v=7(4+8v)-3v | | -25+-40= | | 3550=75x | | 13=13+5(x-2)3 | | 2/3(x+4)=0 | | 1+3p-4p=-4(-12p+9)+3(p-5) | | -5(-5b-3)=7b+12+12 | | 1/6-2/3m=1/4 | | 0=6.6x+4.9x^2 | | -3/4m-11/4m=-7/2 | | 1/3b-2=2 | | 400/150 | | x^4+2*x^3-2000=0 | | 8k-64= | | x^2+2x^2=81 | | 5q+3=2q+18 | | 4t+6=4t+10 | | 2x+55+45=400 | | 3n^2+40=23n | | 6x+3x-6x= | | 0.3x-0.4x+2=-3 |